2020
DOI: 10.3329/bjms.v19i3.45859
|View full text |Cite
|
Sign up to set email alerts
|

Professional values of the nursing students’ Perspective in Jahrom University of medical sciences, 2017

Abstract: Background and Aim: The main goal of nursing is to promote the value of human beings and the dignity of all those who need care. Nursing should not only include scientific knowledge and technical skills, but also a professionin which professional values are acknowledged. The aim of this study was to determine the professional values from the viewpoint of nursing students in Jahrom University of Medical Sciences. Materials and Methods: In this descriptiveanalytical study, 120 students of Jahrom Nursing and Midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The top-rated item in the "activism" dimension in this study was "advance the profession through active involvement in health-related activities," which may be an indicator of nursing students' empowerment in both countries and a nursing program emphasis on improving the profession. This finding is congruent with many other studies (Jahromi et al, 2020;Paşalak et al, 2021). A significant difference was found between the means of the item "participate in public policy decisions affecting distribution of resources" for the two nationalities, with the Jordanian students earning a higher mean score.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The top-rated item in the "activism" dimension in this study was "advance the profession through active involvement in health-related activities," which may be an indicator of nursing students' empowerment in both countries and a nursing program emphasis on improving the profession. This finding is congruent with many other studies (Jahromi et al, 2020;Paşalak et al, 2021). A significant difference was found between the means of the item "participate in public policy decisions affecting distribution of resources" for the two nationalities, with the Jordanian students earning a higher mean score.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies conducted in a variety of countries have reported on nursing student perceptions of professional values and the correlations between these perceptions and demographic characteristics (Arries, 2020;Bleda et al, 2020;Jahromi et al, 2020). The findings of some of these studies indicate perceptions in the "caring" dimension to be the most highly rated, whereas those in the "activism" dimension are the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…It is when they admit an error and analyzes it with a supervisor that students can repair, minimize the consequences and learn from what happened, developing themselves personally and professionally (1) . It is essential to admit and accept responsibility in order to enhance situations in which an error has occurred as a learning opportunity and as a way to ensure care and customer safety (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…But coronavirus is today not only the doctor-patient related issue but it has a public health concern. Another reminder is nursepatient relationship as we know nurses also has a full of values like scientific knowledge, technical skill and professionalism 13 . In social media civic people also make a lot of comments and create a bunch of myths around the novel corona virus 14 .…”
Section: Dear Editormentioning
confidence: 99%